Simple Periscope Design as Optical Learning Media - Doyan, Aris; Ratnasari, Rika (AMPLITUDO : Journal of Science and Technology Innovation, 2022)
Media is needed in the learning process to support practicum activities. Practicum tools can be made with simple materials, but must meet the standards or eligibility of the tool. This study aims to make a practicum tool in the form of a simple periscope as an optical learning medium in schools. Periscope is an optical instrument used to see objects from hidden places. Usually, periscopes are used on submarines. However, in this study a simple periscope was made from a flat mirror which can be used as a learning medium in schools. This research is experimental research with the stages of preparation, manufacture and testing of tools. The simple periscope that has been designed is a flat mirror periscope made of PVC pipe, L pipe, and a flat mirror. The results of a simple periscope test in the field are being able to see objects clearly as far as the eye can see, the image shape obtained is virtual, upright, and the same size, while the focal length is half of the object distance